THE LEARNING STRATEGIES APPLIED BY SOME HIGH SCHOOL STUDENTS IN PREPARING SPEECH CONTEST - Yunita Amelia; Diani Nurhajati; Suhartono Suhartono (LPPM Universitas PGRI Jombang, 2026)
This study aimed to describe the language learning strategies employed by two winners in preparing for an English speech competition at SMAN 1 Kediri. Employing a qualitative case study design, the study focused on the first- and second-place winners of the competition. Data were collected through observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña (2014), involving data condensation, data display, and conclusion drawing and verification. The findings revealed that the participants employed all six categories of language learning strategies proposed by Oxford (1990), namely memory, cognitive, compensation, metacognitive, affective, and social strategies. Among these, cognitive and metacognitive strategies emerged as the most prominent, particularly in organizing ideas, monitoring practice, and enhancing speaking performance. These findings suggest that integrating various learning strategies helps students prepare effectively for English speech competitions.